The effects of aerobic exercise training on oxidant–antioxidant balance, neurotrophic factor levels, and blood–brain barrier function in obese and non-obese men - Roh, Hee-Tae (J Sport Health Sci, 2017)
PURPOSE: The purpose of this study was to investigate the effects of obesity and aerobic exercise training on oxidant–antioxidant balance, neurotrophic factor levels, and blood–brain barrier (BBB) function. METHODS: Ten non-obese healthy men (body mass index < 25 kg/m(2)) and 10 obese men (body mass index ≥ 25 kg/m(2)) were included in the study. Both groups performed treadmill exercise for 40 min 3 times weekly for 8 weeks at 70% heart rate reserve. Blood samples were collected to examine oxidant–antioxidant balance (reactive oxygen species (ROS) and superoxide dismutase (SOD) activity levels), neurotrophic factors (brain-derived neurotrophic factor (BDNF), nerve growth factor, and glial cell line-derived neurotrophic factor levels), and BBB function (S100β and neuron-specific enolase (NSE) levels) before and after exercise training. RESULTS: The obese group showed significantly greater changes than the non-obese group in serum ROS (−0.46 ± 0.31 mmol/L vs. −0.10 ± 0.17 mmol/L, p = 0.005), serum S100β levels (−8.50 ± 5.92 ng/L vs. −0.78 ± 5.45 ng/L, p = 0.007), and serum NSE levels (−0.89 ± 0.54 µg/L vs. −0.01 ± 0.74 µg/L, p = 0.007) after training. At baseline, the obese group showed significantly higher serum ROS and S100β levels and significantly lower serum SOD activity and BDNF levels than the non-obese group (p < 0.05). The obese group showed significantly lower serum ROS, S100β, and NSE levels and significantly higher serum SOD activity and BDNF levels after training compared with baseline (p < 0.05). CONCLUSION: These results suggest that obesity can reduce serum neurotrophic factor levels and can induce BBB dysfunction. On the other hand, aerobic exercise can improve an oxidant–antioxidant imbalance in obese subjects and limit BBB dysfunction.